The effect of different patient-based learning models on student perceptions of empathy, engagement, knowledge, and learning experience - LUKE LEIGH (Medical Teacher, 2024)
Background: Problem-based learning is used widely in pharmacy and medical programmes, incorporating realistic patient scenarios into regular teaching as a way of linking theory to practice. Routine case-based learning lessons ranges from real patient involvement, scripted patient scenarios, digital simulations (avatars) as well as through media such as Zoom. The existing literature has explored the extensive benefits of using patients in clinical education, but fewer studies have directly compared the efficacy of each model as learning tools. Aim: To compare student perceptions of patient-based learning models to elicit student empathy, increase engagement, improve knowledge, and enrich learning experience. Methods: A questionnaire was distributed to second-year pharmacy students in Swansea University to gather their perceptions on the nine different patient-based learning models in their routine teaching (SUMS RESC 2023-0011). Students were asked to rank their experience of the models explicitly against each other, based on the four pillars of (1) eliciting student empathy, (2) increasing engagement, (3) improving knowledge and (4) enriching the learning experience. Students were also asked to rate the significance of realism (i.e. knowing the patient demographics/having a visual representation of the patient) to their experience. Results: Altogether, 31 student rankings of the nine learning models were weighted (9 = highest rank; 1 = lowest ranked). The data showed clear preferences for real-patient involvement over fictional cases, especially for eliciting empathy. Interestingly, scripted scenarios were rated highly for both engagement and learning experience only when avatars were involved, which suggests a role of animated visual representation of the patient in facilitating these outcomes. Conclusion: Whilst it is useful to have multiple patient-based learning models, this study serves as a guide for educators in preparing case-based learning sessions for achieving the desired outcomes of any of the four pillars above.